2022
DOI: 10.1001/jamanetworkopen.2021.46873
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Early-Life Growth and Age at Pubertal Onset in US Children

Abstract: IMPORTANCE Earlier pubertal onset may be associated with an increased risk of chronic diseases. However, the extent to which growth in the first 5 years of life-an important developmental life stage that lays the foundation for later health outcomes-is associated with pubertal onset remains understudied.OBJECTIVE To assess whether changes in weight, length or height, and body mass index (BMI, calculated as weight in kilograms divided by height in meters squared) during the first 5 years of life are associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 84 publications
4
18
0
Order By: Relevance
“…Moreover, the breastfed infants presented a subsequent lower risk of obesity or overweight after four months postnatal [ 47 ]. Studies focusing on early-life growth discovered a negative correlation between weight in late infancy and the timing of menarche [ 48 , 49 ]. Furthermore, the early adiposity rebound (EAR) facilitates understanding this association.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the breastfed infants presented a subsequent lower risk of obesity or overweight after four months postnatal [ 47 ]. Studies focusing on early-life growth discovered a negative correlation between weight in late infancy and the timing of menarche [ 48 , 49 ]. Furthermore, the early adiposity rebound (EAR) facilitates understanding this association.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, there is significant variation in the age of puberty among the same population making it more difficult to generalize based on age ( Ohlsson et al, 2019 ; Aris et al, 2022 ) ( Figure 2E ). Complex genetic, environmental, and nutritional factors can influence normal puberty timing, precocious puberty, and delayed puberty ( Aris et al, 2022 ). The standard variation of puberty age among girls in a country can be as much as 1.5 years ( Hirokawa et al, 1992 ).…”
Section: Policy Options and Implications-life Stages And Age Differ S...mentioning
confidence: 99%
“…Aris et al studied the early-life growth and age at pubertal onset among boys and girls in US children. They found that faster gains in weight, length or height, or body mass index in early life were associated with earlier pubertal onset ( Aris et al, 2022 ), again suggesting that nutrition leads to variation in ages of puberty.…”
Section: Policy Options and Implications-life Stages And Age Differ S...mentioning
confidence: 99%
See 1 more Smart Citation
“…Early puberty in both boys and girls may be associated with a higher risk for immediate and long-term health consequences including dysmetabolism, psychosocial issues and chronic disease ( Aris et al , 2022 ). Delayed puberty may also have both immediate and long-term health effects on both girls and boys, but these effects have not been as clearly established ( Zhu and Chan, 2017 ).…”
Section: Introductionmentioning
confidence: 99%